PENGUATAN SUMBER DAYA MANUSIA NELAYAN DESA LOPO KECAMATAN BATUDAA PANTAI MELALUI PELATIHAN TUNE-UP MESIN KETINTING - Hendra Uloli; Stella Junus; Jamal Darusalam Giu; Irwan Wunarlan; Fentje Abdul Rauf; Muh. Yasser Arafat (Jurnal Abdimas Terapan, 2022)
This community service activity is the second of three years of village service assisted by the Department of Industrial Engineering, Faculty of Engineering UNG which has started in 2020 and will end in 2022. The Department of Industrial Engineering carries out village development service activities in four different locations, one of which is Lopo Village. Batudaa Pantai District. The purpose of this service activity is to increase the potential of Lopo Village human resources through tune-up training for fishing boat propulsion engines (ketinting). The implementation of activities is divided into 3 stages, namely (1). Preparation stage, where surveys and problem identification are carried out. (2). The stages of program implementation are the provision of training materials and practices (3). Reporting and publication of service activities. The results obtained from this service activity are, after the tune-up training, the fishing communities participating in the training are able to tune up the ketinting machine that they use to earn a living independently without having to use professional staff which of course costs money.